Starbucks kluang mall / Muhamad Nur Fahmi Mazalan ...[et al.] - Mazalan, Muhamad Nur Fahmi; Hamidun, Shahril; Shairan, Nur Artikah; Sulaiman, Shadiq Azim (2018)
This study is about the most leading brand and retailer of finest coffee which is Starbucks Coffee Kluang Mall. This store is master franchise around the Malaysia. The company target markets nationally and internationally by selling the best quality coffee and related products, and by providing high class customer service. The reputation of brand name and image of Starbucks allow brand recognition and consumer retention. Therefore, the expanding of stores to other countries is more proficient and easier. Starbucks features a variety of hand-crafted beverages, pastries, a selection of sandwiches and merchandise.